Strength and Deformability of Structural Steel for Use in Construction - Begman Kulbayev; Vladimir Lapin; Alexandr Shakhnovich; Yeraly Shokbarov; Tursymbai Tuleyev; Serik Aldakhov; Yerken Aldakhov; Alimzhan Ali (Salehan Institute of Higher Education, 2024)
The purpose of the study is an experimental determination of the stress-related characteristics of the structural steel produced in the Republic of Kazakhstan for use in conventional and earthquake-resistive construction. Since 2015, the construction industry has been using European regulatory documents—Eurocodes—as a statutory framework. In particular, the Eurocode 1993 for steel structures and the Eurocode 1998 for the design of earthquake-resistant structures However, the study of stress-related properties of structural steel using experimental methods of ISO standards has not been performed. Therefore, in the construction industry of the Republic of Kazakhstan, steel-work structures have been used in fairly limited volume since 2015. The experimental studies were conducted on 7 types of structural steel with thicknesses of 8, 10, and 20 mm manufactured by Arcelor Mittal. The yield strength, ultimate tensile strength (breaking stress), and tensile strength at break were studied. The experimental studies were carried out on the basis of ISO standards. In each test run, 5 samples were used. In two series, 20 samples each were tested, which made it possible to estimate the yield strength and strength distribution functions. The correlation relationships between Brinell hardness and yield and strength limits have been studied. As a result of experimental studies, it was found that the strength and deformability parameters fully comply with the requirements of Eurocode 1993. Based on the application of the Student's test, it is revealed that the distribution functions of yield strength and resistance correspond to the normal law (Gaussian function). The calculation of a three-story, two-span residential building with box section columns for construction in an area with a seismicity of 8 points is performed by the finite element method. The work results will significantly increase the scope of Kazakhstani structural steel use in seismic and conventional areas of the Republic of Kazakhstan. Doi: 10.28991/CEJ-2024-010-03-09 Full Text: PDF